Rational Design and Synthesis of Benzamides as Non-ulcerogenic Anti-inflammatory Agents - Khadse, Saurabh; Ugale, Vinod; Talele, Gokul (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2014)
In an attempt to find a new class of anti-inflammatory agents, a series of novel benzamides 3 (ab1-ab16) was synthesized by utilizing some arylideneoxazolones 2(az1-az4) having 2-acetyloxyphenyl substitution on their second position. IR, 1H-NMR, 13C NMR and HRMS, confirmed the structures of these synthesized compounds. Among the tested benzamide compounds 3ab1, 3ab2, 3ab11 and 3ab16 showed promising anti-inflammatory activity with lessened propensity to cause gastro-intestinal hypermotility and ulceration when compared with standard Indomethacin. Virtual screening was performed by docking the designed compounds into the ATP binding site of COX-2 receptor to predict if these compounds have analogous binding mode to the COX-2 inhibitor.
Keywords: benzamides